21g Vs 22g Ebus-Tbna Needle Sampling And Cell Morphology Of The Core Biopsies And Needle Washings: Is Bigger Better? - Lockman, H; Medford, ARL; Bennett, JA (Bmj Publishing Group, 2024)
Indexed by WOS